A Systematic Review of Efficacy and Safety of Monotherapy and Combination Therapy With Biologic for Stevens-Johnson Syndrome and Toxic Epidermal Necrolysis. Issue 6 (November 2021) - Sachdeva, Muskaan; Maliyar, Khalad; Ponzo, Marisa G.
Background: Biologic drugs have the potential to halt the progression of Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) by decreasing concentrations of tumor necrosis factor-α, a cytokine implicated in epithelial cell death. The objective of this systematic review is to investigate the efficacy and safety of biologic monotherapy and combination therapy for SJS/TEN. Methods: MEDLINE and EMBASE in OVID were searched on October 28, 2020. Inclusion criteria were original studies containing human participants diagnosed with SJS/TEN and treated with biologics. Studies were excluded if they were literature reviews, systematic reviews, letters to the editor, or conference abstracts. Results: The 38 articles reviewed included 27 (71.1%) case reports, 6 (15.8%) case series, 3 (7.9%) retrospective reviews, and 2 (5.3%) RCTs. The age range of the included studies was 2 to 85 years, the mean age was 46.4 years. The mean body surface (BSA) across the 38 included articles was 31.0%. The average actual mortality reported within the 38 included articles was 9.2%. Both biologic monotherapy and combination therapy were associated with improved outcomes in SJS/TEN. Furthermore, anti TNF-alpha therapy, specifically etanercept, showed improved outcomes as monotherapy. Conclusions: Overall, reviewed studies presented a strong case for biologic treatment, both monotherapy and combination use, in SJS/TEN treatment. Based on the number of fatal adverse events observed, biologic monotherapy may be safer compared to combination therapy. Further research with a larger sample size and a randomized control trial design is required.